Proses Pengambilan Suara Anggota Dewan Dalam Suatu Penyusunan Peraturan Daerah Kota Palu - Isman Bruaharja; Reynaldi Hidayat; Saputra Batara Kassa; Siti Bunga Arfa Aulia; Niken Aprilia; Nur Ainun (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2026)
This study analyzes the dynamics of the voting process of members of the Palu City Regional People's Representative Council (DPRD) in the formation of Regional Regulations (Perda). Using a juridical-empirical research method, this study found that although the DPRD's Rules of Procedure provide for open and closed voting mechanisms, decision-making practices are dominated by consensus (acclamation) as a result of political consolidation at the faction level. This voting behavior is significantly influenced by the discipline of party instructions, the validity of technical data in the Academic Paper, and the sociological aspirations of the community regarding spatial planning and land ownership issues. In addition, political instruments such as delays due to quorum and walkouts are identified as bargaining strategies in legislative-executive relations. The study concludes that the direction of council members' votes is the result of negotiations of political interests and considerations of technical rationality of data, which demands strengthened transparency in every stage of legislation.